2019
DOI: 10.5799/jmid.574542
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Urinary Tract Infection and Their Diagnostic Performances among Cameroonian Under-five

Abstract: Objective: Urinary tract infection (UTIs) in child is a serious public health problem especially in developing countries. This study aimed at identifying factors associated with urinary tract infection and determining their diagnosis performances as well as resulting algorithms among Cameroonian under-five. Methods: A descriptive and analytical cross sectional study took place from May 2013 to March 2014 at Pediatrics Department of the Bonassama District hospital in the town of Douala. Urine samples were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 20 publications
(27 reference statements)
0
6
2
Order By: Relevance
“…Contrary to the report from Douala [ 8 ] and elsewhere [ 21 , 28 ] in which females were more at risk than males, our study observed a higher prevalence in males than in females though the difference was not significant. Poor hygiene generally observed with male children must have accounted for this observation.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Contrary to the report from Douala [ 8 ] and elsewhere [ 21 , 28 ] in which females were more at risk than males, our study observed a higher prevalence in males than in females though the difference was not significant. Poor hygiene generally observed with male children must have accounted for this observation.…”
Section: Discussioncontrasting
confidence: 99%
“…Therefore, 24 out of 200 test cases (12%) had UTIs by microscopy, giving a UTI prevalence of 12%. Our prevalence is higher than 11% recently reported in children under 5 in Nigeria [ 21 ] but lower than 32.2% reported in a recent study of children under 5 in Douala, Cameroon [ 8 ], and 65.9% reported in Buea [ 17 ]. Though the prevalence of UTI in our study is relatively low, it is still a cause for concern given that if not promptly diagnosed and adequately treated, it could result in chronic ill health and long-term renal damage.…”
Section: Discussioncontrasting
confidence: 79%
See 3 more Smart Citations